TERMS OF CHEMICAL TREATMENT OF WHEAT BY AIRCRAFT - Юн, Г.; Кандиба, Г. (Science-based technologies, 2012)
The article examines the relationship of growth stages winter wheat with much needed of air chemical work with the timing for the work to protect and stimulation the growth of winter sowing.